PERANCANGAN SISTEM OTOMASI PEMANASAN MINYAK MENTAH BAGIAN FURNACE PADA PROSES PENGOLAHAN MINYAK MENTAH (STUDI KASUS UNIT KILANG PUSDIKLAT MIGAS CEPU) - PERMANA, TIO YUDHA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Pusdiklat Migas Cepu has an oil refinery unit that functions as a unit for processing of crude oil into various products such as pertasol, kerosene, diesel fuel, diesel and residual PH. Processing of crude oil generally consists of a heating process in heat exchanger and furnace, and separation processes in distillation unit. Furnace is a major heating in the heating process that occurs in crude oil refinery unit. Given the importance of this process then the whole process that occurs in the furnace must be monitored and controlled in order to obtain optimal output as desired. design in the crude This study aimed to obtain the automation system oil heating of furnace parts on crude oil refinery at Pusdiklat Migas Cepu. The study began with an analysis of operating data from the data provider to record the flow of crude oil is heated and the flow of fuel oil used for the combustion process in the furnace, and then proceed with the design of Process Flow Diagram (PFD), Piping and Instrumentation Diagram design (P&ID), sensor and actuator design specifications, Functional Diagram design, designing display of Human Machine Interface (HMI), design of architecture based on DCS Yokogawa Centum VP and programming in the final project. and f The results of this research is design of PFD, P&ID, unctional diagram draft, specification sensors and actuators, design of HMI, and design of DCS architecture and program.